(untitled) (Transport systems and technologies, 2018)
The new approach to the estimation of experimental studies results of the brake efficiency of freight wagons, based on the implementation of the data model in the form of a differential equation of the train movement during braking and study of braking processes using computer aided simulation methods is described. The mathematical models which take into account the following principal characteristics of the braking system, i.e. the actual functional dependences of the brake cylinder filling time with compressed air during braking, as well as the nominal forces of pressing the brake pads on the wheel pairs; the net specific resistance to movement; the values of normalized descents are given. The implementation of the estimation procedure is illustrated by the experimental open-top wagon, the braking parameters (brake distances, speeds, deceleration, brake coefficients, actual coefficients of friction, etc.) are given. Keywords: brake efficiency, freight wagon, computer-aided simulation, mathematical